Model Keunggulan Bersaing Untuk UMKM Tempe - Bogy Febriatmoko; Widhian Hardiyanti; Ajeng Aquinia (Equilibrium: Jurnal Penelitian Pendidikan dan Ekonomi, 2022)
Abstract SMEs are a sector that has proven to be resilient in the face of the 1998 monetary crisis. In 2020 the world will be hit by the COVID-19 pandemic, and Indonesia is no exception. Therefore, it is good to continue researching the competitive advantages of tempeh SMEs in the midst of a pandemic condition like now and look at the problem from a comprehensive direction and pay attention to what variables can continue to support competitive advantage. Competitive advantage is an important factor in strategic management. With a competitive advantage, SMEs will be able to continue their business, win the competition and achieve their goals. In this study, primary data was used with the data collection method using a questionnaire that we distributed to 118 Tempe SMEs. Statistical data analysis uses path analysis with SPSS 16 program. The strategies formulated in this research to achieve competitive advantage include market orientation and business performance, where business performance is an intervening variable. From the results of statistical tests conducted in this study, all hypotheses were accepted with significant effect.Keywords: SMEs Competitive Advance, Export SMEs, Indonesian SMEs, Tempe SMEsAbstrakUMKM merupakan sektor yang sudah terbukti tangguh menghadapi badai krisis moneter tahun 1998. Di tahun 2020 dunia dilanda pandemic covid-19 tidak terkecuali Indonesia. Oleh sebab itu baik kiranya untuk terus meneliti keunggulan bersaing UMKM tempe di tengah kondisi pandemic seperti sekarang ini serta melihat permasalahan dari arah yang komprehensif dan memperhatikan variable apa saja yang dapat terus mendukung keunggulan bersaing.. Keunggulan bersaing merupakan faktor penting dalam manajemen strategis. Dengan keunggulan bersaing, UMKM akan dapat melanjutkan bisnisnya, memenangkan persaingan dan mencapai tujuannya. Dalam penelitian ini mnggunakan data primer dengan metode pengumpulan data menggunakan kuesioner yang kami sebar ke 118 UMKM Tempe. Analisis data statistic menggunakan analisis jalur dengan program SPSS 16. Strategi yang dirumuskan dalam riset ini untuk mencapai keunggulan bersaing meliputi orientasi pasar dan kinerja bisnis, dimana kinerja bisnis sebagai variable intervening. Dari hasil uji statistik yang dilakukan dalam penelitian ini bahwa semua hipotesis diterima dengan hasil berpengaruh signifikan.Kata kunci: SMEs Competitive Advantadge; Export SMEs; Indonesia SMEs; Tempe SMEs.